Chitosan Membranes Filled with Cyclosporine A as Possible Devices for Local Administration of Drugs in the Treatment of Breast Cancer - Sonia Trombino; Federica Curcio; Teresa Poerio; Michele Pellegrino; Rossella Russo; Roberta Cassano (Molecules, 2021)
The aim of this work is the design, preparation and characterization of membranes based on cyclosporine A (CsA) and chitosan carboxylate (CC) to be used as an implantable subcutaneous medical device for a prolonged therapeutic effect in the treatment of breast cancer. The choice to use CsA is due to literature data that have demonstrated its possible antitumor activity on different types of neoplastic cells. To this end, CsA was bound to CC through an amidation reaction to obtain a prodrug to be dispersed in a chitosan-based polymeric membrane. The reaction intermediates and the final product were characterized by Fourier transform infrared spectroscopy (FT-IR) and proton nuclear magnetic resonance (1H-NMR). Membranes were analyzed by differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The data obtained showed the effective formation of the amide bond between CsA and CC and the complete dispersion of CsA inside the polymeric membrane. Furthermore, preliminary tests, conducted on MDA-MB-231, a type of breast cancer cell line, have shown a high reduction in the proliferation of cancer cells. These results indicate the possibility of using the obtained membranes as an interesting strategy for the release of cyclosporin-A in breast cancer patients.